2008
DOI: 10.1590/s0103-50532008000100007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amitriptyline and its main metabolites in human plasma samples using HPLC-DAD: application to the determination of metabolic ratios after single oral dose of amitriptyline

Abstract: Foi desenvolvido e validado um método simples e rápido, empregando CLAE-DAD, para a determinação simultânea de amitriptilina, nortriptilina, E-10-hidroxiamitriptilina, Z-10-hidroxiamitriptilina, E-10-hidroxinortriptilina, Z-10-hidroxinortriptilina e desmetilnortriptilina em amostras de plasma humano. O método utiliza extração líquido-líquido em duas etapas e separação isocrática em fase reversa. A precisão apresentou D.P.R. % menor que 12.1% e a precisão esteve na faixa entre 93,1 e 102,5%. O limite de detecçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Another alternative is the use of metabolic ratios obtained at routine therapeutic drug monitoring analyses, when the correlation of these rations and the phenotype of CYP2C19 are well known (Van der Weide et al, 2005). Recent studies demonstrated the correlation of CYP2C19 phenotype with amitriptyline demethylation metabolic ratios, a reaction also catalyzed by CYP2C19 (Linden et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Another alternative is the use of metabolic ratios obtained at routine therapeutic drug monitoring analyses, when the correlation of these rations and the phenotype of CYP2C19 are well known (Van der Weide et al, 2005). Recent studies demonstrated the correlation of CYP2C19 phenotype with amitriptyline demethylation metabolic ratios, a reaction also catalyzed by CYP2C19 (Linden et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Levels of AMI and NOR in biofluids have also been studied through other systems, such as gas chromatography (Gupta, Shah, & Hwang, ), but the prevalent procedures in published methods encompass HPLC (Khatoon, Mohd‐Setapar, Ahmad, & Nian‐Yian, ; Plenis & Bączek, ; Samanidou, Nika, & Papadoyannis, ). Linden and colleagues () described a method for the determination of AMI, NOR, desmethylnortriptyline, E‐OH AMI and Z‐OH AMI, and E‐OH NOR and Z‐OH NOR in human plasma samples using HPLC coupled with a diode array detector. The lower limit of quantification (LLOQ) for all compounds evaluated was 5 ng/mL with complete separation achieved in around 22 min and the CYP2C19 genotype correlating with AMI demethylation ratios in healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method is of great value in determination of the mentioned drugs, because of their improved simplicity and sensitivity, low cost, and free from dependence on expensive instruments and hazardous analytical reagents. [3] …”
Section: Resultsmentioning
confidence: 99%
“…The formation of the E-10-hydroxy metabolites is dependent on the activity of CYP2D6, with stereospecificity to the (−)-EHAT and (−)-EHNT metabolites. The main metabolic pathways of AT and NT in blood are shown in Scheme 1 [3].…”
Section: Introductionmentioning
confidence: 99%